If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -4)(3x + 8) = 18 Reorder the terms: (-4 + 2x)(3x + 8) = 18 Reorder the terms: (-4 + 2x)(8 + 3x) = 18 Multiply (-4 + 2x) * (8 + 3x) (-4(8 + 3x) + 2x * (8 + 3x)) = 18 ((8 * -4 + 3x * -4) + 2x * (8 + 3x)) = 18 ((-32 + -12x) + 2x * (8 + 3x)) = 18 (-32 + -12x + (8 * 2x + 3x * 2x)) = 18 (-32 + -12x + (16x + 6x2)) = 18 Combine like terms: -12x + 16x = 4x (-32 + 4x + 6x2) = 18 Solving -32 + 4x + 6x2 = 18 Solving for variable 'x'. Reorder the terms: -32 + -18 + 4x + 6x2 = 18 + -18 Combine like terms: -32 + -18 = -50 -50 + 4x + 6x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -50 + 4x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-25 + 2x + 3x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-25 + 2x + 3x2)' equal to zero and attempt to solve: Simplifying -25 + 2x + 3x2 = 0 Solving -25 + 2x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -8.333333333 + 0.6666666667x + x2 = 0 Move the constant term to the right: Add '8.333333333' to each side of the equation. -8.333333333 + 0.6666666667x + 8.333333333 + x2 = 0 + 8.333333333 Reorder the terms: -8.333333333 + 8.333333333 + 0.6666666667x + x2 = 0 + 8.333333333 Combine like terms: -8.333333333 + 8.333333333 = 0.000000000 0.000000000 + 0.6666666667x + x2 = 0 + 8.333333333 0.6666666667x + x2 = 0 + 8.333333333 Combine like terms: 0 + 8.333333333 = 8.333333333 0.6666666667x + x2 = 8.333333333 The x term is 0.6666666667x. Take half its coefficient (0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. 0.6666666667x + 0.1111111112 + x2 = 8.333333333 + 0.1111111112 Reorder the terms: 0.1111111112 + 0.6666666667x + x2 = 8.333333333 + 0.1111111112 Combine like terms: 8.333333333 + 0.1111111112 = 8.4444444442 0.1111111112 + 0.6666666667x + x2 = 8.4444444442 Factor a perfect square on the left side: (x + 0.3333333334)(x + 0.3333333334) = 8.4444444442 Calculate the square root of the right side: 2.905932629 Break this problem into two subproblems by setting (x + 0.3333333334) equal to 2.905932629 and -2.905932629.Subproblem 1
x + 0.3333333334 = 2.905932629 Simplifying x + 0.3333333334 = 2.905932629 Reorder the terms: 0.3333333334 + x = 2.905932629 Solving 0.3333333334 + x = 2.905932629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.3333333334' to each side of the equation. 0.3333333334 + -0.3333333334 + x = 2.905932629 + -0.3333333334 Combine like terms: 0.3333333334 + -0.3333333334 = 0.0000000000 0.0000000000 + x = 2.905932629 + -0.3333333334 x = 2.905932629 + -0.3333333334 Combine like terms: 2.905932629 + -0.3333333334 = 2.5725992956 x = 2.5725992956 Simplifying x = 2.5725992956Subproblem 2
x + 0.3333333334 = -2.905932629 Simplifying x + 0.3333333334 = -2.905932629 Reorder the terms: 0.3333333334 + x = -2.905932629 Solving 0.3333333334 + x = -2.905932629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.3333333334' to each side of the equation. 0.3333333334 + -0.3333333334 + x = -2.905932629 + -0.3333333334 Combine like terms: 0.3333333334 + -0.3333333334 = 0.0000000000 0.0000000000 + x = -2.905932629 + -0.3333333334 x = -2.905932629 + -0.3333333334 Combine like terms: -2.905932629 + -0.3333333334 = -3.2392659624 x = -3.2392659624 Simplifying x = -3.2392659624Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.5725992956, -3.2392659624}Solution
x = {2.5725992956, -3.2392659624}
| X+2=-3-2x-8 | | 4a^2(a-1)(6+a)=0 | | 6n-5=61 | | 4x-8=6x+16 | | 3a+b+c=29 | | (x^2)-7x=0 | | 2.6x=23.4 | | 2(v+7)-9=19 | | 2.7=8.3+y | | 2800=.05x+1000 | | 0.4x+0.8=3.2 | | 7.72=2(3.14)(r) | | D=GS | | xy=32 | | 2=18 | | 6=-19-5 | | -10=70 | | 5z-4z=9z-4+z | | x(x)+10x-39=0 | | 6x+4=6(x+5) | | 0.7x=14 | | 5(2x-4)=3x+34 | | 13y+15=2y+4 | | -5+(1+z)=8 | | -5(t-2)+7t=6t-5 | | x^2+1=2x^2+4x-23 | | 15x-2=12x-11 | | 1.7=-0.2x | | 15x-3=27x+5 | | 4x+21=x+9 | | 5z-8-2+2=0 | | 3+y=10-3(y+3) |